The Director's Role in the Community Service Advertisement “Titik Pulang” for the Al - Qomariah Islamic Boarding School Foundation - Cesa S, M. Ragil; Atmaja, Suhendra; Nihayati, Laila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
An This study explores the role of the director in producing the public service advertisement "Titik Pulang" for the Al-Qomariah Islamic Boarding School Foundation. The film aims to introduce moral values to a broader audience, emphasizing the importance of appreciating those around us, particularly family, to avoid regret in the future. Additionally, the film seeks to build a positive image of the Al-Qomariah Foundation as an institution dedicated to education and child protection while providing a safe environment for underprivileged children. The production process involved several stages, including developing the story concept, creating the synopsis, drafting the treatment, and writing the script. After the pre-production phase, the process continued with shooting and editing. As the director, the creator played a strategic role in translating creative ideas into visually communicative and meaningful forms. The director also supervised every detail of the production, ensuring that all elements supported the narrative and maintained the consistency of the conveyed message. The short film "Titik Pulang" was not only designed as an academic requirement to obtain a Bachelor's degree in Communication Studies but also as an educational medium for society. Its moral message is expected to inspire audiences to appreciate family and their surroundings. Moreover, this work aligns with the vision of the Al-Qomariah Foundation in promoting education and child protection as efforts to build a sustainable society for the future